Kidungan Jula-juli in East Java: Media of Criticism and Propaganda (From The Japanese Occupation Era to The Reform Order in Indonesia) - Setiawan, Aris (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This research aims to determine the historical construction of criticism and propaganda formed in Kidungan Jula-juli performance in each era. Kidungan is a song in the Gending Jula-juli in East Java. The musical text presented in the song seems to be open (blak-blakan [openness]), assertive, and emotionally becomes the power of criticism. Historical issues concerning the function of Kidungan Jula-juli are interesting enough to be known, thus encouraging this study to get a basic and detailed understanding of the historical stages of the role of Kidungan Jula-juli from the Japanese era to the reformation era. This study using a historical approach and emphasizes the problem of music function. The analysis was carried out by looking at the ideas, concepts, and cultural references that accompanied the performance of Kidungan Jula-juli. The results of this study indicate the dynamics of the function of criticism and propaganda in Kidungan Jula-juli. During the Japanese occupation era, Kidungan Jula-juli was very sharp in its role as an instrument of the independence movement; from 1950 to 1965, Kidungan Jula-juli was used by political parties to strengthen political support and propaganda. In the New Order Era, kidungan lost the function of criticism.Ã‚Â The state controlled it for the sake of propaganda and the legitimacy of power.Ã‚Â Kidungan Jula-juli is more open and present on a stage with other performing arts in the era of the reform order.